Endothelial Nitric Oxide Synthase Expression Is Progressively Increased in Primary Cerebral Microvascular Endothelial Cells During Hyperbaric Oxygen Exposure. Issue 1 (2009) - Xu, Xiongfei; Wang, Zhongzhuang; Li, Quan; Xiao, Xiang; Lian, Qinglin; Xu, Weigang; Sun, Xuejun; Tao, Hengyi; Li, Runping
Abstract : Exposure to hyperbaric oxygen (HBO) can lead to seizures. Many studies have demonstrated that there exist a very close relationship between the alteration of cerebral blood flow (CBF) and the onset of seizures. Nitric oxide (NO) may play a key role in the change of CBF during exposure, and modulation of endothelial nitric oxide synthase (eNOS)-derived NO by HBO is responsible for early vasoconstriction, whereas late HBO-induced vasodilation depends upon a large amount of NO from both eNOS and neuronal nitric oxide synthase (nNOS). To investigate the effect of HBO on the activity and expression of eNOS in cerebral microvascular endothelial cells (CMEC) in vitro, primarily cultured CMEC from neonatal rats were exposed to oxygen at 500 kPa [5 atmosphere absolute (ATA)] for 10, 20, 30, 60 and 120 minutes (min), then eNOS activity, protein and mRNA contents in cells were detected. Our results showed that immediately after exposure, 30, 60 and 120 min HBO exposures did not alter NOS activity. When detected no matter immediately or six hours (h) after exposure, these exposures also did not alter eNOS protein and mRNA levels. However, when detected 24 h after exposure, 30, 60 and 120 min exposures upregulated eNOS protein content by 39%, 60% and 40% respectively. 10 and 20 min exposures upregulated eNOS mRNA content by about 15%, while 30, 60 and 120 min exposures upregulated it by about 20–30%. The increased eNOS protein and mRNA contents at 24 h after exposure may reflect new protein synthesis for eNOS. Our studies showed that with the exposing protocols we used, HBO did induce eNOS expression increase in CMEC. However, compared with the decrease of CBF in vivo, which occurred in a relative short time after rat was exposed to HBO above 4 ATA, the responses of eNOS in CMEC in vitro were a little slow. Thus we considered that for the vasodilation in the late period of HBO exposure before seizure, the effect of NO produced by eNOS was limited.